Exploration of the Environment, Violence, and Tradition in ”Mata Blater” by Mahwi Air Tawar - Kurniasari Febrianti, Binar; Mahmud, Amir; Ris Riana, Derri; Yulianti, Yeni; Windiyarti, Dara; Syaifuddin; Nurfaidah, Resti; Raudloh, St. (BRIN Publishing (Penerbit BRIN), 2024)
This study aims to analyze the cultural ecology of the short story anthology